Comprehensive biomarker profiling reveals distinct molecular signatures across stone types: a large-scale cross-sectional study in Southern China - Chen, Qingjiang; Huang, Linliang; Wang, Suilin; Wei, Daqiang; Lu, Jiancai; Han, Xiujing; Chang, Zhenglin (Frontiers in Physiology, 2025)
BackgroundStone diseases represent a significant global health burden affecting 10%–15% of the population worldwide. Despite advances in diagnostic imaging, current approaches often lack the ability to predict stone formation or differentiate between stone types at early stages.MethodsThis retrospective study analyzed data from 61,310 stone patients and 55,010 matched controls using 1:1 propensity score matching. Stone cases were categorized into five major groups and further subdivided by organ system. Comprehensive serum biomarker profiling was conducted using automated biochemistry analyzers.ResultsUrinary system stones constituted the largest proportion (80.97%), followed by biliary system stones (21.12%). The study revealed distinct biomarker signatures: elevated serum creatinine and cystatin C in uric acid stones; increased PSA and monocyte counts in prostatic calculi; elevated β2-microglobulin and total bilirubin in common bile duct stones; and increased basophils, ceruloplasmin, ferritin, immunoglobulin-A, and rheumatoid factor in gallstones.ConclusionThis study represents the first comprehensive evaluation of stone-specific clinical biomarker patterns derived from routine laboratory parameters, providing potential diagnostic markers for different stone types and suggesting stone-specific pathophysiological mechanisms.